Methods of Understanding the Quran and Hadith from Ancient Times to Modern Times - Zekkour, Hafidha; Imamuddin, Imamuddin (PT. Pusmedia Group Indonesia, 2024)
Along with the development of science and technology and rapid social change, the method of understanding the Qur'an and Hadith faces increasingly complex challenges. Traditional methods that have been used so far are beginning to be questioned in their ability to answer increasingly complex and global contemporary problems. The emergence of various new schools of thought, both liberal, contextual, and progressive, increasingly enrich and at the same time complicate efforts to understand the Qur'an. The purpose of this study is to discuss the Method of Understanding the Qur'an and Hadith from Ancient Times to Modern Times. The method used is the literature study method. In this method, data collection techniques are taken from reference sources in the form of books, journals, scriptures or other sources. The results of this study explain that The Quran and Hadith are the main sources of Islamic teachings that have encouraged scholars to develop various methods of interpretation. Although the methods of interpretation differ between the classical and modern eras, the main goal remains the same: to facilitate the understanding and application of Islamic teachings and to draw closer to Allah. The classical era emphasized fiqh, linguistic, and rational interpretation, while the modern era developed scientific, social, and feminist methods of interpretation. Differences in the context of time, tradition, and human conditions have encouraged Muslim scholars to continuously adapt their interpretive approaches to remain relevant and meaningful